2021
DOI: 10.1002/hbe2.301
|View full text |Cite
|
Sign up to set email alerts
|

A review of phishing attacks and countermeasures for internet of things‐based smart business applications in industry 4.0

Abstract: Due to the advancement in industry 4.0, cybercrimes in internet‐based business applications are rapidly increasing. To encounter such attacks, the intruders use various tools and techniques such as Phishing, Malware, SQL Injection, Ransomware, Cross‐Site Scripting (XSS), Denial of Service (DoS), Session Hijacking, and Credential Reuse. Phishing is most commonly in practice in the current digital era. Phishing is a fraudulent attempt to obtain sensitive information from deceiving users. These types of cyber‐att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Study [6] used decision tree, a nonlinear classifier to generate tree and rules. For analyzing results, the J48 algorithm is used as an analyzing tool.…”
Section: Relate Workmentioning
confidence: 99%
“…Study [6] used decision tree, a nonlinear classifier to generate tree and rules. For analyzing results, the J48 algorithm is used as an analyzing tool.…”
Section: Relate Workmentioning
confidence: 99%
“…It has become part of our daily lives, especially for younger age groups; it is easy to access and use. That is a highly significant consideration when youth cannot access traditional health services; the Internet also provides them with a health service and a safe and secure health information database [12,13].…”
Section: Cognitive Defectsmentioning
confidence: 99%
“…A study disclosed that cyberattacks had a severe impact on companies [5], and 61% of small and medium enterprises have suffered cyberattacks [6]. Similarly, another study revealed that cybersecurity risks, like data breaches and disclosure of confidential data, are on the rise due to the increased use of cloud technologies and online applications [7].…”
Section: Introductionmentioning
confidence: 99%